Noise comfort level in Malaysian airport: Kuala Lumpur International Airport & Sultan Abdul Aziz Shah Airport / Rozrinda Roslan - Roslan, Rozrinda (Faculty of Architecture, planning and Surveying, 2014)
The airport industry, like other industries, is facing the effects of increasing environmental pressure which is a pollution sources that may harm the surround environment. Aviation industry is one of the industries that contribute sort of pollutes to environmental damages such as noise pollution, air pollution and water pollution as for local level and global warming as for global level (Badriyah,2010). Therefore, the airport management will look on ways to manage airport efficiently and at the same time meet environment requirement. This research on the noise comfort level for the Malaysian airport, Kuala Lumpur International Airport and Sultan Abdul Aziz Shah Airport, hence as to interprets to come out with the integration that can be implement to maintain and enhance the noise comfort level. This research had been accomplish by using three method of research which are by collecting the noise level data by using a Sound Level Meter (SLM), an interviews at the management level and the distribution of the questionnaires to the users. There are two case studies that been chosen which are Kuala Lumpur International Airport (KLIA) and Sultan Abdul Aziz Shah (Subang) Airport. From this research, the total average noise level that been obtained at Kuala Lumpur International Airport is at 41 decibels whereas 49 decibels for Sultan Abdul Aziz Shah (Subang) Airport. Kuala Lumpur International Airport been implemented a very integrated design on the terminal itself as to address the noise pollution impact towards indoor of the building whereas Sultan Abdul Aziz Shah (Subang) Airport implemented more on the additional material that may reduce the impact. The average user at Kuala Lumpur International Airport agreed that the noise level at an indoor of the airport is at the comfort level but the users at Sultan Abdul Aziz Shah (Subang) Airport were not agreed that the noise level of the indoor is at the comfort level since the noise level is exceeds the permissible level.